Answer:
-.75x-6
Explanation:
Step 1: simplify the first equation
1/4(x-28)=2x, or .25x-7=2x.
Step 2: simplify the second equation so that one side equals 2x
13-5x=-7.5x-t. Add 7x to either side to get 13+2x=-.5x-t. Then, subtract 13 from either side and then you have 2x=-.5x-t-13
Step 3: make both equations into one equation
Since 2x=.25x-7, and 2x=-.5x-t-13, then it's safe to say .25x-7=-.5x-t-13.
Step 4: Simplify this final equation
Add .5x to both sides to get .75x-7=-t-13. Then add 13 to both sides to get .75x+6=-t. Then multiply everything by -1 to get -.75x-6=t